Digital Poetics and Transcreation: A Computational Study of Rabindranath Tagore’s Gitanjali - Ghosh, Arun Kumar (International Journal of Research in Interdisciplinary Studies, 2025)
Abstract—The research investigates Rabindranath Tagore's Gitanjali (1912) through translation and transcreation and digital poetics perspectives. The research develops a computational framework to study Gitanjali's bilingual text in Bengali and English, which exposes statistical language and emotional shifts that standard literary analysis fails to identify. The research demonstrates through stylometric and sentiment-mapping analysis that Tagore achieved a unique aesthetic language through self-translation, which combined devotional intensity with universal accessibility. The research combines digital humanities with translation theory to establish transcreation as an epistemic literary production method, which transforms translation into a creative process of renewal. The research establishes a vital knowledge gap in Tagore studies while transforming digital methods for analyzing postcolonial literary works.